(untitled) (Baghdad Science Journal, 2012)
All the prepared metal complexes of Pt (IV), Au(III), Rh (III), Co (II) and V(IV) with new ligand sodium [5-(p-nitro phenyl)-/4-phenyl-1,2,4-triazole-3-dithiocarbamato hydrazide] (TRZ.DTC) have been synthesized and characterized in solid state by using flame atomic absorption, elemental analysis C.H.N.S, FT-IR ,UV-Vis Spectroscopy, conductivity and magnetic susceptibility measurements. The nature of the complexes formed in ethanolic solution has been studied following the molar ratio method also was studied stability constant and found to be stable in molar ratio1:1 of VL (IV) and CoL(II) while Pt(IV), Au(III) and Rh(III) complexes stable in molar ratio 1:2 as well as the molar absorptivity for these complexes were calculated. From the previous analyses, octahedral geometry was suggested for Pt (IV), Rh (III) and Co (II) complexes, square planar was suggested for Au(III) complex while V(IV) complex has a square pyramidal. Cytotoxic effect of PtL, AuL and RhL as well as ligand has been evaluated against RD cell line by using four different concentrations (500, 250, 125 & 62.5 µg/ml) respectively in three exposure times 24, 48 and 72 hrs and compared this effect with control positive Cis-Pt.